2017
DOI: 10.1371/journal.pone.0178779
|View full text |Cite
|
Sign up to set email alerts
|

Time course of VCAM-1 expression in reperfused myocardial infarction in swine and its relation to retention of intracoronary administered bone marrow-derived mononuclear cells

Abstract: BackgroundIntracoronary infusion of autologous bone marrow-derived mononuclear cells (BMMNC), after acute myocardial infarction (AMI), has been shown to improve myocardial function. However, therapeutic efficacy is limited, possibly because cell retention rates are low, suggesting that optimization of cell retention might increase therapeutic efficacy. Since retention of injected BMMNC is observed only within infarcted, but not remote, myocardium, we hypothesized that adhesion molecules on activated endotheliu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
(34 reference statements)
1
5
0
Order By: Relevance
“…Furthermore, the time course of VCAM-1 release was evaluated by Uitterdijk et al on swine. 27 They reported a significant increase in sVCAM-1 expression during the first week after MI followed by a decrease up Here, we demonstrated that sVCAM-1 is an early biomarker of severity after STEMI and is correlated with IS, LVEF, and LV remodeling. sVCAM-1 appeared as an efficient predictor of negative clinical outcome as illustrated by the ROC curve, superior to a classic marker of IS such as creatine kinase.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Furthermore, the time course of VCAM-1 release was evaluated by Uitterdijk et al on swine. 27 They reported a significant increase in sVCAM-1 expression during the first week after MI followed by a decrease up Here, we demonstrated that sVCAM-1 is an early biomarker of severity after STEMI and is correlated with IS, LVEF, and LV remodeling. sVCAM-1 appeared as an efficient predictor of negative clinical outcome as illustrated by the ROC curve, superior to a classic marker of IS such as creatine kinase.…”
Section: Discussionsupporting
confidence: 56%
“…Mulvihill et al 26 found a sustained sVCAM‐1 increase up to 6 months following an ACS. Furthermore, the time course of VCAM‐1 release was evaluated by Uitterdijk et al on swine 27 . They reported a significant increase in sVCAM‐1 expression during the first week after MI followed by a decrease up to 1 month.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that the integrin α 4 + ASCs subpopulation highly expressed integrin α 4 on their surface, and their binding partner of VCAM-1 was up-regulated in the infarcted myocardium. VCAM-1 expression peaked at 3 days post-MI and recovered to normalization 14 days post-MI ( 16 ). VCAM-1 expression correlated well with the extent of bone marrow (BM)-MSCs retention at 3 days and 7 days post-MI ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…35 However, there are a number of target receptors expressed on the cell surface under ischemia: for examples, some cell adhesion molecules including VCAM-1, ICAM-1 are highly expressed. 36 Since the level and timing of the expression are different among those receptors during the ischemia, it is unclear that which receptors should be the responsible target for MSC delivery. For example, the E-selectin expression level reached the plateau at around 12 h after occlusion.…”
Section: Discussionmentioning
confidence: 99%